Analisis Determinan Kejadian Berat Bayi Lahir Rendah (BBLR) di RSUD Tani dan Nelayan - Hafid, Wahyuni; Badu, Fraining Deisi; Laha, Lili Pramutia (Universitas Gorontalo, 2018)
Low Birth Weight (LBW) has a contribution to infant mortalityespecially during perinatal period. According to the World HealthOrganization (WHO), there are 15.5% or 20.6 million babies born withBirth Weight (LBW) every year, and 96.5% are in developing countries.Nationally, the target of LBW that is set at the target of NutritionImprovement Program toward Healthy Indonesian is 7% maximum. Thisresearch is an analytic quantitative research using cross sectional studydesign. The study was conducted in March - April 2017. The instrumentused a questionnaire sheet. The sample in this study as many as 137respondents taken by purposive sampling. Hypothesis testing using chisquare test. The statistical test of chi square test showed a significantrelationship between mother education (ᴩ = 0,000 <0,05), mother parity(ᴩ = 0,000 <0,05), and antenatal care (ANC) (ᴩ = 0,000 <0,05) with theincidence of LBW in Regional Public Hospital (RPH) Tani dan Nelayan inBoalemo District of Gorontalo Province. Maternal, parity and antenatalcare (ANC) education is the determinant factor of Low Birth Weight (LBW)occurrence at Regional Public Hospital (RPH) Tani dan Nelayan inBoalemo District of Gorontalo Province in 2017. It is expected that theactive role of health personnel in providing information and education tothe community related to maternal and child health through theimprovement of integrated health services post and pregnancyexamination.